Uji fitokimia dan aktivitas antioksidan biji petai cina (Leucaena leucocephala (Lam.) de. wit) pada umur buah berbeda - Mayta Novaliza Isda; Titin Nilasari (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Chinese petai (Leucaena leucocephala (Lam.) De. Wit) is a plant that is much sought after by the public because of its benefits. The most exploited part of the Chinese locust seed is the seed. This study aims to determine the content of secondary metabolites and antioxidant activity in Chinese petai seeds (L. leucocephala) at different fruit ages. Phytochemical tests were carried out qualitatively. The antioxidant activity test was carried out using the 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) method. The research result shows that Chinese petai seeds had the same amount of tannin, but the young pods and seeds contained more saponins and flavonoids, while the semi-old and old seeds contained more alkaloids and triterpenoids. The antioxidant activity test shows that the methanol extract of the pods had a strong IC50 (Inhibitory Concentration 50%) value, which is (99.79 µg/mL) compared to young seeds (1126.11 µg/mL), semi-old seeds (16629.48 µg/mL). mL) and old seeds (835.30 µg/mL) were categorized as inactive. Generally, phytochemical tests show that methanol extracts of pods, young seeds, semi-old seeds, and old seeds contain secondary metabolite compounds, namely alkaloids, flavonoids, triterpenoids, tannins, and saponins.